2019
DOI: 10.1101/529230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping of transgenic alleles in plants using a Nanopore-based sequencing strategy

Abstract: Transgenic technology was developed to introduce transgenes into various organisms to validate gene function and add genetic variation for the development of beneficial input or output trait over 40 years ago. However, the identification of the transgene insertion position in the genome, while doable, can be cumbersome in the organisms with complex genomes. Here, we report a Nanopore-based sequencing method to rapidly map transgenic alleles in the soybean genome. This strategy is high-throughput, convenient, r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…SMS is considered to be a very effective method for deciphering complex genome structures and filling in the gaps of NGS in reference genome assembly (18). Since 2019, various researchers have demonstrated the possibility of TGS at the whole-genome level for molecular characterisation of transgenic animals and plants (19). Osamu et al identified a single transgene insertion and confirmed a large genomic deletion during transgene insertion in a transgenic mouse strain (20).…”
Section: Introductionmentioning
confidence: 99%
“…SMS is considered to be a very effective method for deciphering complex genome structures and filling in the gaps of NGS in reference genome assembly (18). Since 2019, various researchers have demonstrated the possibility of TGS at the whole-genome level for molecular characterisation of transgenic animals and plants (19). Osamu et al identified a single transgene insertion and confirmed a large genomic deletion during transgene insertion in a transgenic mouse strain (20).…”
Section: Introductionmentioning
confidence: 99%